Delegation and Recruitment in Organizations: The Slippery Slope to "Bad" Leadership - Çakir Selcen; Matakos Konstantinos; Tukiainen Janne (Aboa Centre for Economics, 2025)
We construct a dynamic model of two-sided sorting in labor markets with multi-dimensional agent and firm heterogeneity. We apply it to study optimal party structure and the decision of how (de)centralized candidate recruitment should be. Parties are non-unitary actors and compete at the local markets over recruitment of competent candidates and local organizers possess an informational advantage over the distribution of politicians’ skill, which is positively related to electoral rent generation. Party leadership has a dual objective: they want simultaneously to maximize a) the organization’s rents and b) their retention probability. Thus, when deciding how centralized recruiting should be, leaders face a trade-off: while delegating candidate selection to local party organizations might increase the party’s electoral returns, it also limits a leader’s ability to stack the organization with loyalists who are more likely to retain her when she faces a (stochastic) leadership challenge. We characterize an equilibrium delegation rule with two key properties: a) some high-skilled politicians may select into lower performing parties due to ideological alignment, and b) more extreme and incompetent leaders delegate less and as a result, survive longer at the helm of a shrinking party. Thus, our findings highlight the slippery slope to authoritarian and persistently "bad" leadership. Our model can be applied to other labor recruitment settings.